Iodine dynamics in soil - Hassan Shetaya, Waleed Hares Abdou (2011)
The principal aim of this investigation was to understand the transformation and reaction kinetics of iodide and iodate added to soil in relation to soil properties. In addition, to integrate the data into a predictive model of iodide and iodate sorption kinetics parameterised by soil properties. Solid phase fractionation coupled with solution phase speciation (HPLC-ICPMS) was used to follow the assimilation of 129I- and 129IO3- spikes into ‘steady state’ soil microcosms. The extraction efficiency of tetra-methyl ammonium hydroxide (TMAH) for soil iodine, and the effects of experimental procedures and conditions on the speciation of extracted iodine were tested. Moreover, the possibility of extracting ‘reactive’ inorganic iodine forms sorbed on soil metal oxides by competition with PO43- ions was investigated. Results showed that changing TMAH concentration, extraction time, extraction temperature or soil particle size did not generally affect the concentrations of total iodine extracted. The ratio of iodide to total iodine in the TMAH extracts varied with the extraction conditions which led to the conclusion that part, or all, of the measured iodide is possibly produced by hydrolysis of organic iodine forms. This conclusion was also confirmed by the detection of high concentrations of iodide in TMAH extracts of a humic acid. Only iodide was measured in the phosphate extracts of soil and it constituted up to 33% of the total iodine in the KH2PO4 extracts which indicates that most of the iodine mobilised by KH2PO4 is organically bound. When soil / KH2PO4 suspensions were spiked with 129I- and 129IO3-, at least 50% of 129I- and 15% of 129IO3- were recoverable after 72 hours of reaction. The lowest recoveries were observed with the highest concentration of KH2PO4, which also mobilised the greatest concentrations of DOC, indicating that although KH2PO4 is capable of releasing sorbed iodide and iodate in soil, it may also promote iodide and iodate reaction with soil organic matter. Iodine content of soil biomass was determined following chloroform fumigation of soil. The concentrations of total iodine in fumigated soil samples were only marginally higher than iodine concentration in the control samples indicating that microbial biomass iodine constitutes only a small fraction of total soil iodine (0.01 – 0.25 %). The change in iodine (129I) solubility and speciation in nine soils with contrasting properties (pH, Fe/Mn oxides, organic carbon and iodine contents), incubated for nine months at 10oC and 20oC, was also investigated. The rate of 129I sorption was greater in soils with large organic carbon contents, low pH and at higher temperatures. Loss of iodide (129I-) from solution was extremely rapid, apparently reaching completion over minutes-hours; iodate (IO3-) loss from solution was slower, typically occurring over hours-days. In all soils an apparently instantaneous sorption reaction was followed by a slower sorption process for IO3-. For iodide a faster overall reaction meant that discrimination between the two processes was less clear. Instantaneous sorption of IO3- was greater in soils with high Fe/Mn oxide content, low pH and low organic content, whereas the rate of time dependent sorption was greatest in soils with higher organic contents. Phosphate extraction (0.15 M KH2PO4) of soils, ~100 h after 129I spike addition, indicated that concentrations of sorbed inorganic iodine (129I) were very low in all soils suggesting that inorganic iodine adsorption onto oxide phases has little impact on the rate of iodine assimilation into humus. Transformation kinetics of dissolved inorganic 129IO3- and 129I- to sorbed organic forms was modelled using a range of reaction and diffusion based approaches. Irreversible and reversible first order kinetic models, and a spherical diffusion model, adequately described the kinetics of both IO3- and I- loss from the soil solution but required inclusion of a distribution coefficient (Kd) to allow for instantaneous adsorption. A spherical diffusion model was also collectively parameterised for all the soils studied by using pH, soil organic carbon concentration and combined Fe + Mn oxide content as determinants of the model parameters (Kd and D/r2). From the temperature-dependence of the sorption data the activation energy (Ea) for 129IO3- transformation to organic forms was estimated to be ~43 kJ mol-1 suggesting a reaction mechanism slower than pore diffusion or physical adsorption, but faster than most surface reactions.